2019
DOI: 10.17265/2159-5828/2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Production and Evaluation of Table Wine Using Two Different Varieties of Pawpaw (Carica papaya)

Abstract: The aim of this study was to produce and evaluate table wine from two different varieties of pawpaw (rose red and yellow pawpaw). The must was evaluated for physicochemical and microbiological changes during fermentation while the wine was analyzed for physicochemical characteristics, microbiological quality and sensory properties and compared with commercial grape wine. Specific gravity of the "must" during fermentation decreased from 1.059-0.995 for rose red pawpaw and 1.005-0.990 for yellow pawpaw. The suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 17 publications
6
8
0
Order By: Relevance
“…Meanwhile, the results reported in this study showed that TA of the fermenting 'must' steadily increased from 0.45-0.68 g/mL within the 14 days fermentation period. According to Kiin-Kabari and Igbo [41], wine is supposed to have a titratable acidity within the range 0.5-1.0% and the wine produced in this study met this requirement.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Meanwhile, the results reported in this study showed that TA of the fermenting 'must' steadily increased from 0.45-0.68 g/mL within the 14 days fermentation period. According to Kiin-Kabari and Igbo [41], wine is supposed to have a titratable acidity within the range 0.5-1.0% and the wine produced in this study met this requirement.…”
Section: Discussionmentioning
confidence: 76%
“…Critically, the increasing concentration of alcohol in the fermenting 'must' most likely created an unconducive environment for microorganisms to thrive with the exception of yeast cells which decreased in population between Day 7 and 14 [12]. Bacterial growth was inhibited by alcohol by plasmolyzing the cell wall of the bacteria [41]. According to Mathew et al [36], the possible reasons for the decrease in population of yeast cells as reported in their study include high cell density, depletion of nutrients, suspected presence of toxic metabolic byproducts as well as rupturing of cell membrane of the yeast cells by increasing concentration of alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations